دیارترین هۆزە نیشتەجێیەکانی بەری مەرگە و دۆڵی جافایەتی - شوانی, پ. ی. د. ئاکۆ عەبدولکەریم; عەزیز, شاباز محەمەد (Sulaimani Journal for Humanities, 2023)
Interest in the history of a nation, clan, or tribe indicates interest in the etiquette, traditions, and social norms of those human groups that live in a specific geographical location, and the region we are talking about; It is a rugged and mountainous geography, and that nature made it a stronghold for revolutionaries and revolutions throughout history, due to the difficulty of the enemies reaching it to chase the revolutionaries. In this research, we are talking about the regions of (Marjah) and (Bangerd), this region is inhabited by a mixture of clans i n terms of its population composition, and each component of those communes has its own traditions and customs, all these tribes came to the region from different spots, so we cannot determine in what form The original inhabitants of the region and the tribes that inhabited it in the past, but we can confirm that the tribes inhabiting it now have migrated to it for various reasons and motives, and its original inhabitants migrated to other regions, and in both cases there are many motives and reasons for these events, Of which: First / political motives and obstacles by successive federal governments in Iraq. Secondly/ the economic factor of the migration of tribes in search of sources of livelihood and making a living, since the region and its economic resources do not provide for their livelihood. Thirdly/ there is the case of the harshness of the climate, especially in the winter, when those tribes were forced to migrate to other areas that are more suitable for living, but despite all these events, the region (Deja Javti, Marga, and Bengerd) remained the best support for the Kurdish revolutions since the days of the revolution of Sheikh Mahmoud and Then the September revolution and the new Kurdish revolution after the setback of 1975.